Підвищення надійності і економічності роботи турбін фірми «Вумаг» - Мисак, Йосиф; Івасик, Ярослав; Басюк, Тарас (Видавництво Національного університету «Львівська політехніка», 2001)
In this work we propose the technical decision intended to raise reliability and economy of turbines that have been moved in regime with deteriorating vacuum.